Neuronal p38α mediates age‐associated neural stem cell exhaustion and cognitive decline. Issue 6 (27th September 2019) - Moreno‐Cugnon, Leire; Revuelta, Miren; Arrizabalaga, Olatz; Colie, Sandra; Moreno‐Valladares, Manuel; Jimenez‐Blasco, Daniel; Gil‐Bea, Francisco; Llarena, Irantzu; Bolaños, Juan Pedro; Nebreda, Angel R.; Matheu, Ander
Abstract: Neuronal activity regulates cognition and neural stem cell (NSC) function. The molecular pathways limiting neuronal activity during aging remain largely unknown. In this work, we show that p38MAPK activity increases in neurons with age. By using mice expressing p38α‐lox and CamkII‐Cre alleles ( p38α∆‐N ), we demonstrate that genetic deletion of p38α in neurons suffices to reduce age‐associated elevation of p38MAPK activity, neuronal loss and cognitive decline. Moreover, aged p38α∆‐N mice present elevated numbers of NSCs in the hippocampus and the subventricular zone. These results reveal novel roles for neuronal p38MAPK in age‐associated NSC exhaustion and cognitive decline. Abstract : With aging, neurons accumulate p38MAPK activity. Neuronal inactivation of p38alpha delays neural stem cell (NSC) exhaustion and maintains cognition at advanced age.